Infant HIV infection despite "universal" antenatal testing. Issue 1 (12th September 2007) - Struik, S S; Tudor-Williams, G; Taylor, G P; Portsmouth, S D; Foster, C J; Walsh, C; Hanley, C; Walters, S; Smith, J H; Lyall, H
Abstract : We reviewed the antenatal HIV testing history, clinical presentation and outcome of 25 infants diagnosed with HIV between 1 January 2001 and 31 December 2005 in a tertiary referral hospital in London. Of the 25 cases, 21 had received antenatal care in the UK. Twelve mothers had not had an antenatal HIV test, four had tested positive antenatally, while five had had a negative HIV test on antenatal booking, implying seroconversion in pregnancy. When mothers had not been diagnosed antenatally, infants presented with severe infections, which were fatal in six cases. The majority (65%) of the children have long-term neurological sequelae. HIV seroconversion is an important cause of infant HIV in the UK.